Pemenuhan Hak Atas Penghasilan Yang Layak Bagi Kurir Ekspedisi Dalam Perspektif Keadilan Ekonomi - Nanda Sesilia Isabel; Tomy Michael (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The development of the expedition service industry in Indonesia has increased along with the growth of electronic commerce, making couriers an essential part of the goods distribution process. However, the increasing demand for delivery services has not been fully followed by the fulfillment of couriers’ rights, particularly the right to receive a decent income. The diverse relationship patterns between expedition companies and couriers, either through employment relationships or partnerships, create issues regarding income certainty, legal protection, and the balance between workload and compensation. This study aims to analyze the fulfillment of the right to a decent income for expedition couriers from the perspective of economic justice and to examine the necessary legal protection for couriers’ welfare. This research uses a normative legal method with statutory and conceptual approaches. The results indicate that couriers’ economic rights still face challenges due to income systems based on delivery volume and the absence of adequate minimum income standards. These conditions demonstrate an imbalance between labor contributions, occupational risks, and compensation received. Therefore, stronger regulations and policies are needed to ensure legal certainty, social protection, and decent income for expedition couriers based on the principles of economic justice.